2013
DOI: 10.1177/004005991304500302
|View full text |Cite
|
Sign up to set email alerts
|

Helping Students with Moderate and Severe Intellectual Disability Access Grade-Level Text

Abstract: Teaching students with moderate and severe intellectual disability who are early readers or nonreaders to engage with grade-level text is challenging. How can teachers promote text accessibility and teach text comprehension? This article describes research-based strategies educators can use to adapt grade-level text and teach text comprehension for students with moderate and severe intellectual disability who are early readers or nonreaders. These approaches can support teachers in developing materials and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 3 publications
2
30
0
2
Order By: Relevance
“…Educators can assist students with intellectual disabilities by implementing an evidence-based intervention to enhance the ERC process (Hudson, Browder, & Wakeman, 2013). One strategy that has shown some success in increasing the ERC skills of students with and without disabilities, but that has not demonstrated success with kindergarten students with intellectual disabilities, is one version of a metacognitive reading strategy.…”
Section: Educational Issue Declarationmentioning
confidence: 99%
See 2 more Smart Citations
“…Educators can assist students with intellectual disabilities by implementing an evidence-based intervention to enhance the ERC process (Hudson, Browder, & Wakeman, 2013). One strategy that has shown some success in increasing the ERC skills of students with and without disabilities, but that has not demonstrated success with kindergarten students with intellectual disabilities, is one version of a metacognitive reading strategy.…”
Section: Educational Issue Declarationmentioning
confidence: 99%
“…These constructive theories clearly supported the framework of this study. In other words, when the kindergarten students with intellectual disabilities were given specific clues about reading content, these clues appeared to create metacognitive aids that facilitated ERC skills (Bilgi Damber, 2015;Hudson & Browder, 2014;Hudson et al, 2013;Shurr & Taber-Doughty, 2012;Qanwal & Karim, 2014;Wood, Browder, & Flynn, 2015).…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we found no research on literacy interventions with preschool children with moderate to severe disabilities, recommendations from studies with preschool children with speech and language impairments point to the importance of explicit teaching and providing multiple opportunities to learn the skill (Carta & Driscoll, 2013 ). Research with older students has found that specifi c adaptive strategies (e.g., adapting text, offering response options, using a hierarchy of least prompts) have been effective in increasing access to age-appropriate literacy materials (Hudson, Browder, & Wakeman, 2013 ). Researcher-designed e-books that integrate principles of Universal Design for Learning with technology have been effective in promoting the development of comprehension skills for elementary students with moderate and severe disabilities (Coyne, Pisha, Dalton, Zeph, & Smith, 2012 ).…”
Section: Oral Languagementioning
confidence: 99%
“…Several papers have been published for teachers of students with learning disabilities (LD; Haager & Vaughn, 2013; Graham & Harris, 2013; Scruggs, Brigham, & Mastropieri, 2013), intellectual disabilities (Hudson, Browder, & Wakeman, 2013), and Autism (Constable, Grossi, Moniz, & Ryan, 2013). …”
Section: Ccss: Heightened Reading Complexity and Associated Challengesmentioning
confidence: 99%